2012
DOI: 10.1111/j.1365-2133.2012.10917.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical vitamin D3 analogues induce thymic stromal lymphopoietin and cathelicidin in psoriatic skin lesions

Abstract: Topical VD3As induce TSLP and cathelicidin in psoriatic lesions, resulting in suppression of IL-12/23 p40, IL-1α, IL-1β and TNF-α, thereby ameliorating psoriatic plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 50 publications
1
55
0
Order By: Relevance
“…These findings are consistent with epidemiological data suggesting that patients with allergic skin inflammation are protected from skin cancer (5)(6)(7)(8). TSLP expression and its immune effects in the skin can be induced by calcipotriol (calcipotriene), an FDA-approved topical medication for psoriasis (9)(10)(11). To determine the efficacy of TSLP induction as a novel immunotherapeutic approach for cancer, we investigated the effect of calcipotriol on skin carcinogenesis in genetically engineered mouse models and in patients with actinic keratosis.…”
Section: Introductionsupporting
confidence: 69%
“…These findings are consistent with epidemiological data suggesting that patients with allergic skin inflammation are protected from skin cancer (5)(6)(7)(8). TSLP expression and its immune effects in the skin can be induced by calcipotriol (calcipotriene), an FDA-approved topical medication for psoriasis (9)(10)(11). To determine the efficacy of TSLP induction as a novel immunotherapeutic approach for cancer, we investigated the effect of calcipotriol on skin carcinogenesis in genetically engineered mouse models and in patients with actinic keratosis.…”
Section: Introductionsupporting
confidence: 69%
“…Previous studies (38-42) have implicated CAMP/LL-37 in some autoimmune diseases, including skin disorders. LL-37 levels do not decline during successful treatment of psoriatic plaques and, in fact, increase when lesions are treated with topical vitamin D3 analogs (41). Furthermore, previous studies have indicated that LL-37 treatment may promote ovarian cancer (43) and lung cancer (44).…”
Section: Discussionmentioning
confidence: 97%
“…Sato-Deguchi et al (25) reported that hCAP-18/LL-37 mRNA expression is increased by treatment with OCT in the skin tissues from psoriasis patients. Taken together, these observations suggest that active metabolites of vitamin D induce hCAP-18/LL-37, which is capable of inducing innate immune defense and providing a promising therapeutic target involving gingival/oral epithelial cells against periodontal pathogen infection.…”
Section: Discussionmentioning
confidence: 99%